Analisis Sistem Diplomasi Digital Pada Website Indonsia Youth Foundation Dengan Metode Importance Performance Analysis - Zakira Putri Setyadi; Asrul Sani (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
This paper discusses the role of information technology in the context of digital diplomacy within the framework of a public diplomacy organization, with a focus on the Indonesia Youth Foundation (IYF). Digital diplomacy represents a new paradigm in diplomacy that leverages information technology and social media to expand reach and influence public opinion globally. IYF, as an organization committed to educating and empowering the youth of Indonesia, has embraced information technology as a primary tool to achieve its goals. By analyzing the role of information technology in digital diplomacy within the context of IYF, this paper provides insights into how public diplomacy organizations can harness the advancements in information technology to accomplish their objectives in promoting positive messages, expanding networks, and building stronger relationships with a global audience. This research is expected to offer practical guidance for similar organizations seeking to enhance the effectiveness of their diplomacy through the utilization of information technology.